Impact of Training Program to Nurses Regarding Complementary Feeding in Infant and Young Children: An Educational Interventional Study - Kayastha, Pawana; Mathema, Smriti; Chikanbanjar, Vijaya; Manandhar, Sunil Raja (Birat Journal of Health Sciences, 2022)
Introduction: Under nutrition is an underlying cause of more than one third of global deaths in children below the age of 5 years. Nutrition education is a critical strategy of intervention to improve child complementary feeding practices which will subsequently decrease mortality and morbidity of under-5 children. Objective: To determine the knowledge of nurses on complementary feeding practices and also provide appropriate training and verify its effectiveness. Method: It is a hospital based educational interventional study. The time-series was from October 2021 to march 2022 included 24 nursing staff. The nurses underwent one-day training on complementary feeding practices in infant. They were evaluated periodically on their knowledge at four different time points. The effectiveness of training was calculated based on the change in scores, as per mean numeric scores, immediately, 1 and 6 months after the training. Result: The nurses showed high competence by obtaining above average scores (100%) by all participant immediately after training and remained so after 1 month. The mean test score obtained before training was 15.3 which increased to 23 after training, 21.9 after 1 month and 17.8 after 6 months of training. The differences in mean were statistically significant (p value 0.000). Conclusion: This training intervention improved knowledge of nurses regarding complementary feeding practices, but improvements need to be strengthened and sustained.